Model Konseling Intensif Progresif Adaptif dan Struktur (KIPAS) - Devi Damayanti; Nilam Anggieta Tirta Sari; Dhiya Khofifah; Bakhrudin All Habsy (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
KIPAS model counseling is a form of counseling that is rooted in Indonesian cultural values. This culture-based approach is believed to be able to change the existing belief system, so that it can encourage the desired behavior change. The method used in this study is qualitative with the type of literature study. Literature study is a method used to collect data or sources relevant to the topic discussed in a research. This method is carried out by collecting data from various sources of literature, such as books, journals, articles, and other documents that are related to the research topic. The purpose of this study is to find out in depth about the model of Structural Adaptive Intensive Intensive Counseling (KIPAS). The findings of this study are discussed: (1) History of Structural Progressive Intensive Counseling (KIPAS), (2) Definition of Structural Adaptive Intensive Counseling (KIPAS), (3) Structural Adaptive Intensive Counseling (KIPAS) form model, (4) Structural Adaptive Progressive Intensive Counseling (KIPAS) steps, (5) Disadvantages and advantages of Structural Adaptive Progressive Intensive Counseling (KIPAS)